Impact of Commodity Futures on Inflation : Perception and Reality - Babshetti, Vaijanath; Basanna, Prakash (Indian Journal of Research in Capital Markets, 2019)
Though it has been proved in many studies that commodity futures trading has a negligible effect on inflation, the relationship between commodity futures trading and inflation cannot be denied completely. In order to curb inflation, the Government of India banned futures trading on wheat, rice, tur, and urad in January 2007 and on chickpea, potato, rubber, and soybean on May 7, 2008. We, in the current study, examined the impact of commodity futures trading on inflation by considering seven agricultural commodities. The current study considered the wholesale price index of the above-mentioned commodities during the 5 year period from 2007 to 2011. Though there were evidences wherein the futures trading influenced the spot prices thereby causing inflation, the ban on futures trading is not the solution to curb inflation. The realistic approach to curb inflation lies in identifying all the factors causing for price rise instead of banning futures trading on selected commodities and waiting for a positive outcome.